Clinicopathological risk factors of Stage II colon cancer: results of a prospective study. (27th March 2013) - Santos, C.; López‐Doriga, A.; Navarro, M.; Mateo, J.; Biondo, S.; Martínez Villacampa, M.; Soler, G.; Sanjuan, X.; Paules, M. J.; Laquente, B.; Guinó, E.; Kreisler, E.; et al.
Abstract Aim Adjuvant 5‐fluorouracil based chemotherapy has demonstrated benefit in Stage III colon cancer but still remains controversial in Stage II. The aim of this study was to analyse the prognostic impact of clinicopathological factors that may help guide treatment decisions in Stage II colon cancer. Method Between 1996 and 2006 data from patients diagnosed with colorectal cancer at Hospital Universitari Bellvitge and its referral comprehensive cancer centre Institut Català d′Oncologia/L'Hospitalet were prospectively included in a database. We identified 432 patients with Stage II colon cancer operated on at Hospital Universitari Bellvitge. The 5‐year relapse‐free survival (RFS) and colon‐cancer‐specific survival (CCSS) were determined. Results The 5‐year RFS and CCSS were 83% and 88%, respectively. Lymphovascular or perineural invasion was associated with RFS [hazard ratio (HR) 1.84; 95% CI 1.01–3.35]. Gender (women, HR 0.48; 95% CI 0.23–1) and lymphovascular or perineural invasion (HR 3.51; 95% CI 1.86–6.64) together with pT4 (HR 2.79; 95% CI 1.44–5.41) influenced CCSS. In multivariate analysis pT4 and lymphovascular or perineural invasion remained significantly associated with CCSS. We performed a risk index with these factors with prognostic impact. Patients with pT4 tumours and lymphovascular or perineural invasion had a 5‐year CCSS of 61%vs the 93% (HR 5.87; 95 CI 2.46–13.97) of those without any of these factors. Conclusion pT4 and lymphatic, venous or perineural invasion are confirmed as significant prognostic factors in Stage II colon cancer and should be taken into account in the clinical validation process of new molecular prognostic factors.